Modeling of Loess Soaking Induced Impacts on a Metro Tunnel Using a Water Soaking System in Centrifuge - Yuwei Zhang; Xiaolin Weng; Zhanping Song; Yufeng Sun (Geofluids)
The collapsibility is one of the key properties for loess. Harmful impacts on the metro tunnels could be obviously subjected to the soaking collapsibility in collapsible loess. However, loess soaking cannot be effectively modeled by the existing centrifugal test equipment (CTE) due to its inherent limitations. In the present paper, a water soaking system (WSS) was improved based on the existing CTE for simulating various loess soaking conditions. The WSS was made of a water storage subsystem and a water distribution subsystem. Some tests were conducted to show the capability of the improved WSS in centrifugal model tests firstly, then it was used to carry out centrifugal model tests on a metro tunnel under full-range and half-range foundation soaking conditions with different soaking depths. The impacts of various soaking conditions on the mechanical properties of the metro tunnel were discussed in detail.